Cyclosporine A and tacrolimus reduce the amount of GLUT4 at the cell-surface in human adipocytes: increased endocytosis as a potential mechanism for the diabetogenic effects of immunosuppressive agents - Pereira, Maria João (2015)
Context:Immunosuppressive agentes are associated with profound metabolic side effects including new-onset diabetes and dyslipidemia after organ transplantation. Objective: Toi nvestigated the effects of the cyclosporine A(CsA)or tacrolimus ong lucose uptake and insulin signalling in human adipocytes and their impact on the regulation of celular trafficking of the glucose transporter 4 (GLUT4). Design:Human isolated adipocytes were incubated with therapeutic concentrations of either CsA or tacrolimus, and glucose uptake and expression of insulin signaling proteins were assessed. Furthermore,we studied effects of CsA and tacrolimus on the regulation of celular trafficking of the GLUT4 in differentiated human pre-adipocytes and L6 cells. Results:CsA and tacrolimus had a concentration-dependent inhibitory effect on basal and insulin stimulated 14C-glucose uptake in adipocytes. Although phosphorylation at Tyr1146 of insulin receptor (IR) was inhibited by tacrolimus, the phosphorylation and/or protein levels of the insulin signalling proteinsIRS1/2,p85-PI3K,PKB,AS160 and mTORC1,as well as GLUT4 and GLUT1,were unchanged by CsA or tacrolimus. Furthermore, CsA and tacrolimus reduced the GLUT4 amount localized at the cell surfasse of differentiated human pre-adipocytes and L6 cells in the presence of insulin.This occurred by na increased rate of GLUT4 endocytosis,with no change in the exocytosis rate. Conclusions: These results suggest that therapeutic concentrations of CsA and tacrolimus can inhibit glucose uptake independente of insulin signalling by removing GLUT4 from the cell surface via na increased rate of endocytosis.Such mechanisms can contribute to the development of insulin resistance and diabetes associated with immunosuppressive therapy.In addition,they may provide novel pharmacological approaches for treatment of diabetes.